The research on giant complex system using intelligent decision support system - Li, J.; Wang, A. (Journal of Digital Information Management, 2013)
Mankind is confronted with an increasingly complex system, especially the major decision issues, such as organization and management, coordination, planning, forecasting, controlling and so on. Due to the complexity of the system, many fuzzy factors and the limitations of the existing complex giant system theory, there are still many problems to be solved. The research on the giant complex system based on the theory of fuzzy decision theory theoretically had been proving the reliability of the group decision and has established "the multijudgments information" fuzzy synthesis computational method. It has designed the corresponding multipurpose intelligent decision support system IDSS.
Keywords: Artificial intelligence; Decision support system; Fuzzy processing; Giant complex system